L’APPORT DE LA FEMME RURALE DANS LA GESTION DURABLE DE LA FORET : CAS D’ALIBUKU (BALI) ET DE LUBUTU (KUMU) - Yvette Nyalusala Ikando; Alphonse Mbate Lupiki (IJRDO Journal of Forestry, wild life and Environment, 2020)
This article studies the place of rural women in decision-making bodies in the Democratic Republic of the Congo, more specifically in the territory of Alibuku and Lubutu. Today, in different countries of the world, women are struggling more and more to gain their autonomy, and this at the political, economic, social and cultural level. In this respect, the question of gender relations, relations between men and women becomes a fundamental element in the choices that will have to be made for the sustainable development of the world. This empowerment of women seems all the more important in the light of the role that they are readily recognized in the resolution of conflicts, and this at a time when practically all the countries of the region have been or are still in the grip of the wars. more violent, wars in which the first victims remain civilians, especially women and children. The exploitable forest, a natural resource that has become both national and international heritage, and contributing to the maintenance of the ecosystem balance, is a source of income for most of the communities on which their lives depend. Hence there is a need to watch over its protection and sustainable management, which must involve locally the participation not only of men, but also of women whose role is recognized as undeniable and questionable throughout the world from country to country. another and from one community to another. Goal 3 of the Millennium Development Goals launched by the United Nations in 2000 aimed to promote gender equality and the empowerment of women. In 2002, the action plan of the World Summit on Sustainable Development, organized in Johannesburg (South Africa), recommended the development of national indicators related to gender equality.